2002
DOI: 10.1034/j.1600-0463.2002.1101204.x
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Legionella pneumophila serogroup 5 outbreak associated with persistent colonization of a hospital water system

Abstract: An outbreak of infections caused by Legionella pneumophila serogroup 5 was detected in a university hospital, and nosocomial reservoirs of the legionella epidemic were examined. Clinical isolates from two patients who had been affected by the L. pneumophila serogroup 5 outbreak, and from another patient with a legionella infection caused by the same serogroup 3 years later, were compared to L. pneumophila serogroup 5 isolates from the hospital water supply by two molecular methods, amplified fragment length po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 31 publications
1
36
0
7
Order By: Relevance
“…In hospitals micro-aspiration may be an important route of transmission for patients lacking normal respiratory reflexes (Yu 2000). In many outbreaks hot water systems are the most frequently involved source of infection (Meenhorst et al 1985;Berthelot et al 1998;Fields et al 2002;Perola et al 2002). Temperature is in fact one of the main factors associated with the presence of legionellae, which are able to reproduce between 20 and 45°C, and can remain viable at much higher temperatures, even up to 60°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hospitals micro-aspiration may be an important route of transmission for patients lacking normal respiratory reflexes (Yu 2000). In many outbreaks hot water systems are the most frequently involved source of infection (Meenhorst et al 1985;Berthelot et al 1998;Fields et al 2002;Perola et al 2002). Temperature is in fact one of the main factors associated with the presence of legionellae, which are able to reproduce between 20 and 45°C, and can remain viable at much higher temperatures, even up to 60°C.…”
Section: Introductionmentioning
confidence: 99%
“…Community-acquired cases of Legionella infection have, for example, been linked to exposure to water systems of hotels (Joseph et al 1996;Benin et al 2002;Fields et al 2002) where a risk is created by the intermittent use of the water and the consequent stagnation, leading to the formation of biofilms in the piping. Furthermore, the presence of L. pneumophila in hospital water supplies is a well-known risk factor for nosocomial pneumonia (Colville et al 1993;Berthelot et al 1998;Perola et al 2002); there is also evidence of a widespread diffusion of the bacteria in domestic hot water distribution systems (Stout et al 1992;Marrie et al 1994;Zacheus and Martikainen 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In a German study of hot-water samples from 452 households, water temperature was observed to be probably the most important factor for the multiplication of legionellae (25). Furthermore, it has been observed for many outbreaks of Legionnaires' disease that hot water was the most frequent source of infection (5,11,20,29). To bridge the gap to cultivation, we isolated and characterized 15 Legionella sp.…”
Section: Discussionmentioning
confidence: 99%
“…In 1995, shock heat treatment was applied at a hospital in Finland after an outbreak of Legionnaires' disease caused by Legionella pneumophila serogroup 5 (15). A shock heat treatment unit was installed after a single round of shock heat treatment had failed.…”
Section: Heat Treatmentmentioning
confidence: 99%